Comparison of soil features and communities of bacteria and arthropod between old growth and logged forest in Sabah - Junia Anilik (2018)
A key driver of land-use change in the tropics is commercial selective logging, which often results in changes to soil biological, chemical and physical properties. Understanding the changes in these properties is essential to evaluate the ecosystem functions of forests after a disturbance. The objectives of this research was 1) to investigate the abiotic (physicochemical) difference between old growth forest soil and logged forest soil; 2) to determine the biotic difference (microbial biomass, leaf-litter arthropod abundance and bacterial community) of soils in old growth and logged forest; and 3) to investigate the relationship between soil abiotic and biotic properties of old growth and logged forest. Soil and arthropod litter samples were collected from old growth forest (OG) and logged forest (LF) in the Stability of Altered Rainforest Ecosystem (SAFE) Project, Sabah. Soils were separated into three parts based on the layer depth. It was found that the organic layer of the logged forest had the highest phenolic content (8.08±4.72 ug/ml) compared to old growth forest (4.63±1.92 ug/ml). Dissolved organic carbon was also found to be higher in logged forest (0.64±0.16 ppm/g) than old growth forest (0.30±0.11 ppm/g). Meanwhile, old growth forest had soils, which have a higher pH, organic matter and moisture content. Discriminant analysis showed that old growth and logged forest organic layer (0) were discriminated from organic mineral (OM) and mineral layer (M). The dominant parameter for OG-O was organic matter while total phenols was associated with LF-O. The trend continued with microbial biomass carbon being higher in logged forest (1.75±1.10 mg/g) than old growth forest (0. 79±0.57 mg/g) indicating logged forest having an active decomposition by microbial community Proteobacteria (30.3%) and P/anctomycetes (15.0%) dominated organic layer of old growth forest while Actinobacteria (30.5%), Proteobacteria (23.1%) and Firmicutes (14.7%) are found to be dominant in logged forests. An average of 123.73±70.1 (17 taxa) arthropod individuals from old growth forest and 45.59±26.7 (15 taxa) individuals from logged forest were found. While the abundance was significantly different between forest types, the community composition did not significantly change. Multivariate analysis revealed that soil properties are potential regulators of the arthropod community composition based on its functional group. We conclude that both old growth and logged forest gave significant difference based on selected physical and chemical properties and affects the faunal communities. Based on the results from this investigation, there are sufficient evidence to proof that logging practices to have a reducing impact on the ecosystem function of the tropical rainforest. However, further data is needed to give a more detailed description of the effected ecosystem functions.